High-affinity CD16 integration into a CRISPR/Cas9-edited CD38 locus augments CD38-directed antitumor activity of primary human natural killer cells. Issue 2 (8th February 2022) - Clara, Joseph Andrew; Levy, Emily R; Reger, Robert; Barisic, Stefan; Chen, Long; Cherkasova, Elena; Chakraborty, Mala; Allan, David S J; Childs, Richard
Abstract : Background: Adoptive transfer of natural killer (NK) cells with augmented antibody-dependent cellular cytotoxicity (ADCC) capabilities and resistance to CD38 targeting has the potential to enhance the clinical anti-myeloma activity of daratumumab (DARA). Therefore, we sought to develop an efficient CRISPR/Cas9-based gene editing platform to disrupt CD38 expression (CD38 knockout (KO)) in ex vivo expanded NK cells and simultaneously arm CD38 KO NK cells with a high-affinity CD16 (CD16-158V) receptor. Methods: CD38 KO human NK cells were generated using Cas9 ribonucleoprotein complexes. The platform was expanded by incorporating messenger RNA (mRNA) transfection of CD38 KO NK cells and targeted gene insertion at the CD38 locus to mediate gene knockin (KI). The capacity of these gene-edited NK cells to persist and mediate ADCC in the presence of DARA was tested in vitro and in a MM.1S xenograft mouse model. Results: Highly efficient CD38 gene disruption was achieved in ex vivo expanded NK cells without affecting their proliferative or functional capacity. CD38 KO conferred resistance to DARA-induced NK cell fratricide, enabling persistence and augmented ADCC against myeloma cell lines in the presence of DARA in vitro and in a MM.1S xenograft mouse model. CD38 KO NK cells could be further modified by transfection with mRNA encoding a CD16-158V receptor, resulting in augmented DARA-mediated ADCC. Finally, we observed that a homology-directed repair template targeted to the CD38 locus facilitated an efficient 2-in-1 CD38 KO coupled with KI of a truncated CD34 reporter and CD16-158V receptor, with CD38 KO /CD16 KI NK cells demonstrating a further enhancement of DARA-mediated ADCC both in vitro and in vivo. Conclusions: Adoptive immunotherapy using ex vivo expanded CD38 KO /CD16 KI NK cells has the potential to boost the clinical efficacy of DARA. By incorporating complementary genetic engineering strategies into a CD38 KO manufacturing platform, we generated NK cells with substantially augmented CD38-directed antitumor activity, establishing a strong rationale for exploring this immunotherapy strategy in the clinic.